2018
DOI: 10.1002/ece3.3827
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing habitat suitability for a central‐place forager in a dynamic marine environment

Abstract: Characterizing habitat suitability for a marine predator requires an understanding of the environmental heterogeneity and variability over the range in which a population moves during a particular life cycle. Female California sea lions (Zalophus californianus) are central‐place foragers and are particularly constrained while provisioning their young. During this time, habitat selection is a function of prey availability and proximity to the rookery, which has important implications for reproductive and popula… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
24
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 25 publications
(27 citation statements)
references
References 93 publications
2
24
0
1
Order By: Relevance
“…To our knowledge, this study provided the longest duration of telemetry data available for AFSSLs and the first winter dataset for AFSSLs in SEAK and western Alaska. Similar to previous studies of AFSSL (Loughlin et al 1998, Andrews et al 2002 and other species of lactating sea lions (Thompson et al 1998, McHuron et al 2016, Briscoe et al 2018, habitat use varied considerably within and among individual AFSSLs during this study. Overall, movements and diving behaviors of AFSSLs from SEAK resembled the seasonal distribution of predictable forage fish, whereas individuals from western Alaska utilized a variety of marine ecosystems, providing new insights into the foraging ecology of AFSSLs from those areas.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…To our knowledge, this study provided the longest duration of telemetry data available for AFSSLs and the first winter dataset for AFSSLs in SEAK and western Alaska. Similar to previous studies of AFSSL (Loughlin et al 1998, Andrews et al 2002 and other species of lactating sea lions (Thompson et al 1998, McHuron et al 2016, Briscoe et al 2018, habitat use varied considerably within and among individual AFSSLs during this study. Overall, movements and diving behaviors of AFSSLs from SEAK resembled the seasonal distribution of predictable forage fish, whereas individuals from western Alaska utilized a variety of marine ecosystems, providing new insights into the foraging ecology of AFSSLs from those areas.…”
Section: Discussionsupporting
confidence: 88%
“…, Briscoe et al. ), habitat use varied considerably within and among individual AFSSLs during this study. Overall, movements and diving behaviors of AFSSLs from SEAK resembled the seasonal distribution of predictable forage fish, whereas individuals from western Alaska utilized a variety of marine ecosystems, providing new insights into the foraging ecology of AFSSLs from those areas.…”
Section: Discussionmentioning
confidence: 58%
“…Despite this, the choice and simulation of pseudo‐absence data can influence model outcomes (Barbet‐Massin et al., ). CRWs are regularly used for simulating pseudo‐absence tracks (Briscoe et al, ; Hazen et al, , ; Willis‐Norton et al, ); however, no simulation method is capable of fully capturing where animals were not present (Aarts, MacKenzie, McConnell, Fedak, & Matthiopoulos, ). CRWs can result in biases, particularly when animals conduct long‐distance movements.…”
Section: Discussionmentioning
confidence: 99%
“…While it is well established that recording the patterns of time-activity budgets in central-place foraging can provide information on foraging traits such as habitat use and diet (e.g. Lamb, Satgé, & Jodice, 2017; Briscoe et al, 2018), fewer studies have revealed their potential for analysing keystone ontogenetic traits (e.g. Lambin & Yoccoz, 2001; Gopukumar, 2003; Benton, St Clair, & Plaistow, 2008; Fay, Barbraud, Delord, & Weimerskirch, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…However, bio-logging applications are still restricted to birds (particularly seabirds, e.g. Rishworth et al, 2014; Fay et al, 2016; Lamb et al, 2017), fishes (Gurarie et al, 2016) and mammals (Lambin & Yoccoz, 2001; Gopukumar, 2003; Gurarie, Andrews, & Laidre, 2009; Briscoe et al, 2018). Very few studies were conducted on insects (but see Degen et al, 2016 for bees), despite the recent availability of adapted miniaturized devices (Kissling, Pattemore, & Hagen, 2014; Nunes-Silva et al, 2019).…”
Section: Introductionmentioning
confidence: 99%